A stationary impulse-radar system for autonomous deployment in cold and temperate environments. Issue 81 (17th April 2020) - Mingo, Laurent; Flowers, Gwenn E.; Crawford, Anna J.; Mueller, Derek R.; Bigelow, David G.
Abstract: Stationary ice-penetrating radar (sIPR) systems can be used to monitor temporal changes in electromagnetically sensitive properties of glaciers and ice sheets. We describe a system intended for autonomous operation in remote glacial environments, and document its performance during deployments in cold and temperate settings. The design is patterned after an existing impulse radar system, with the addition of a fibre-optic link and timing module to control transmitter pulses, a micro-UPS (uninterruptable power supply) to prevent uncontrolled system shutdown and a customized satellite telemetry scheme. Various implementations of the sIPR were deployed on the Kaskawulsh Glacier near an ice-marginal lake in Yukon, Canada, for 44–77 days in summers 2014, 2015 and 2017. Pronounced perturbations to englacial radiostratigraphy were observed commensurate with lake filling and drainage, and are interpreted as changes in englacial water storage. Another sIPR was deployed in 2015–2016 on ice island PII-A-1-f, which originated from the Petermann Glacier in northwest Greenland. This system operated autonomously for almost a year during which changes in thickness of the ice column were clearly detected.